Combination Treatments of Plasma Exchange and Umbilical Cord-Derived Mesenchymal Stem Cell Transplantation for Patients with Hepatitis B Virus-Related Acute-on-Chronic Liver Failure: A Clinical Trial in China. (4th February 2019) - Xu, Wen-xiong; He, Hong-liang; Pan, Shun-wen; Chen, Yuan-li; Zhang, Mei-ling; Zhu, Shu; Gao, Zhi-liang; Peng, Liang; Li, Jian-guo
Abstract : Background . Hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) is a common type of liver failure with a high mortality. This study aimed at investigating the safety and efficacy of the combination treatment of plasma exchange (PE) and umbilical cord-derived mesenchymal stem cell (UC-MSCs) transplantation for HBV-ACLF patients. Methods . A total of 110 HBV-ACLF patients treated in our hospital from January 2012 to September 2017 were enrolled into this trial and divided into the control group (n = 30 ), UC-MSC group (n = 30 ), PE group (n = 30 ), and UC-MSC + PE group (n = 20 ) based on their treatments. The hepatic function, coagulation, and virological and immunological markers were assessed at baseline and 30, 60, 90, 180, and 360 days. The endpoint outcomes were death and unfavorable outcome (need for liver transplantation or death). Results . The UC-MSC + PE group had the lowest rates of death and unfavorable outcome at 30 days, 60 days, and 90 days posttreatment among the four groups, but the difference did not reach significances. The multivariate logistic regression analysis demonstrated that hemoglobin, prothrombin activity, and MELD (model for end-stage liver disease) score were the independent factors associated with the unfavorable outcome (allP < 0.05 ). The levels of total bilirubin, alanine aminotransferase, aspartate transaminase, and MELD score were significantly decreased during treatments (allP < 0.05 ). Conclusion . UC-MSCs combined with PE treatment had good safety but cannot significantly improve the short-term prognosis of HBV-ACLF patients with as compared with the single treatment. The long-term efficacy should be further evaluated. This trial is registered with registration no.NCT01724398 .